SPK MENENTUKAN SUPPLIER BAHAN BAKU PEMBUATAN KERUPUK MENGGUNAKAN METODE AHP - Kelvin; Zyad Rusdi (Jurnal Ilmu Komputer dan Sistem Informasi, 2023)
Suppliers are one of the factors that are very influential in the factory business, especially food manufacturing factories, such as one of the snacks in Bangka, namely crackers. Therefore, to be able to determine reliable suppliers for the quality of their goods, a system is needed to make decisions. The Decision Support System (DSS) uses the Analytic Hierarchy Process (AHP) method which will be used to assist the AB factory in determining which suppliers whose raw material quality is suitable for use at affordable prices. Raw material supplier data is in accordance with the results of interviews and observations with the factory owner so that the system is made according to the owner's wishes. The resulting output results are also in accordance with the desired raw materials.